Communication Strategy of Makassar City Election Commission in Recruitment of Election Committee Organizers - Riyani Riyani; Muh Akbar; Syamsu Rizal (Newinera Publisher, 2024)
The purpose of the study is to find out and describe the communication strategy of the Makassar City Election Commission in recruiting KDP organizers for the 2024 Election has been carried out or not, as well as to know and explain the challenges faced by the Makassar City Election Commission in recruiting KDP organizers for the 2024 Election. The research was conducted at the Makassar City KPU (General Election Commissions) Office. This type of research uses a qualitative approach, with 4 (four) informants. Data collection techniques consist of observation, interview guidelines and documentation. Data analysis techniques use qualitative analysis with three stages, namely data reduction, data presentation, data verification, and conclusions. The results of the study found that the communication strategy applied by the KPU in recruiting KDP organizers for the 2024 election has been well implemented through the KPU website, and is also maximized on social media in the form of Instagram, Facebook, YouTube and Twitter). Furthermore, the communication strategy was implemented by conducting socialization in the form of recruitment banners on all channels and making press conferences so that the public knew information on KDP receipts organized by the Makassar City KPU. The challenges to the communication strategy of the KPU in the 2024 election related to the implementation of KDP recruitment are several things, namely macro problems, technical problems, and ad hoc HR problems.